PARADOX OF THE COERCIVE CONSENT WITHIN THE THEORY OF THE SOCIAL CONTRACT - Savanović, Aleksandar (Politeia, 2019)
In this paper we will analyse some preconditions that must be met by a social contract that pleads to be valid one. When do we accept a contract as a valid agreement? There are some important classic issues, many of them are still open for discussion. With regard to this, we focus on the on the following question: Is a contract the result of free will? What is (if any) the meaning of the phrase ‘coercive agreement’ or ‘coercive consent’? There are two extreme positions: acceptance of coercive agreement without any preconditions or rejection of coercive agreement by some deontological presumption or structural/logical contradiction claim.
Keywords: social contract; coercion; consent